Neuro-imaging characteristics of sensory impairment in cerebral palsy; a systematic review - A. C. S. Knijnenburg; A. C. S. Knijnenburg; C. V. M. Steinbusch; C. V. M. Steinbusch; C. V. M. Steinbusch; Y. J. M. Janssen-Potten; Y. J. M. Janssen-Potten; Y. J. M. Janssen-Potten; Y. J. M. Janssen-Potten; A. Defesche; R. J. Vermeulen; R. J. Vermeulen (Frontiers Media S.A., 2023)
BackgroundObjective: To identify and examine neural reorganization of the sensory network in terms of lesion type, somatotopic organization of the primary somatosensory area, and functional connectivity in relation to sensory function in children and young adults with cerebral palsy (CP).MethodsDesign: systematic review, Prospero registration ID 342570. Data sources: PubMed; Cochrane; Web of Science; Embase; CINAHL and PEDro from inception to March 13, 2021. Eligibility criteria: All types of original studies, concerning sensory connectivity in relation to sensory outcome in patients with spastic CP, <30 years of age. No publication status or date restrictions were applied. Data extraction and synthesis: Two authors independently determined the eligibility of studies. Quality assessment was performed by a third author. Neuro-imaging/neurophysiological techniques, sensory outcomes and patient characteristics were extracted.ResultsChildren and young adults with periventricular leucomalacia (PVL) lesions have significantly better hand function and sensation scores than patients with cortical-subcortical/middle cerebral artery (MCA) lesions. Ipsilesional reorganization of the S1 (primary somatosensory cortex) area appears to be the primary compensation mechanism after a unilateral early brain lesion, regardless of the timing of the lesion. Interhemispheric reorganization of the sensory system after early brain lesions is rare and, when it occurs, poorly effective. Diffusion tractography shows a positive correlation between the ascending sensory tract (AST) diffusivity metrics of the more affected hemisphere and sensory test outcomes.Discussion and conclusionsBecause of the large variability in study design, patient characteristics, neuroimaging/neurophysiological techniques and parameters as well as sensory assessment methods used, it is difficult to draw definite inferences on the relationship between the reorganization of the sensory network following early brain damage and sensory function in children and young adults with CP. In general, sensory function seems to be worse in cortical as opposed to white matter tract (PVL) lesions. International consensus on a clinically relevant sensory test battery is needed to enhance understanding of the intriguing compensatory mechanisms of sensory network following early brain damage and potential consequences for rehabilitation strategies.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/.